Anti-inflammatory Potential of Mangosteen Pericarp Extract (Garcinia mangostana L.) - Auw Natasha Felicia Karnadi; Tjie Kok (FITOFARMAKA: JURNAL ILMIAH FARMASI, 2023)
Mangosteen pericarp (Garcinia mangostana L.) has been used as an active ingredient in numerous traditional medicine formulations. However, their function as an anti-inflammatory agent has yet to be fully understood. Macrophage migration inhibitory factor (MIF) is a mediator that is essential for the development of pro-inflammatory reactions. Hence, MIF activity is often associated with inflammatory diseases and its inhibition could therefore be used as an approach to assess the potential of a material as anti-inflammatory agent. In this study, MIF was exposed with mangosteen pericarp extracts in order to assess the possible anti-inflammatory effect of the extract. The type of mangosteen pericarp extract that possesses the greatest potential as MIF inhibitor and its IC50 value were determined. Based on the results, n-hexane extract of mangosteen pericarp possesses the activity as MIF inhibitor with an IC50 of 4.24 mg/L, and therefore could potentially be used as an anti-inflammatory agent.